FABRICATION OF SURFACE ENHANCED RAMAN SPECTROSCOPY (SERS) SUBSTRATES AND EXAMPLE APPLICATIONS - Agustiana, Elis
Raman spectroscopy is a spectroscopic method that can be used to detect and identify certain substances or materials at the molecular level. The measured Raman signal intensity is weak in some situations, such as observations for analytes at low concentrations. As a result, the signal must be enhanced. Surface Enhanced Raman Spectroscopy (SERS) is one technique that can be used to boost the strength of the Raman signal. To enable accurate identification of the molecules detected, the substrate utilised in the SERS approach has a specific degree of roughness. This substrate can have roughness in the form of gratings, nanorods, nanoparticles, and more. This research aims to fabricate SERS whose particle size can be controlled to produce optimum enhancement. The SERS fabricated uses a gold-coated Digital Versatile Disk (DVD) and ZnO thin film. The SERS substrate was first evaluated using Methylene Blue as a test analyte. Subsequently, the ability of the substrate to detect various target molecules was explored by testing its performance with four common explosives (TNT, PETN, Tetryl and RDX) and commercial pesticides (DDT and CaCO3). Silicon was chosen as a reference substrate due to its smooth surface and stable optical properties. In this study, the SERS substrate's performance was compared to the silicon substrate by measuring the Raman signals for Methylene Blue, TNT, and commercially available pesticides. The experimental results revealed significant signal enhancement using the fabricated SERS substrates. The SERS-DVD substrate exhibited a 172-fold increase in signal intensity compared to the silicon substrate for the Methylene Blue analyte. Similarly, the ZnO thin film SERS substrate demonstrated a 14-fold enhancement for Methylene Blue compared to silicon. For the TNT explosive, the SERS-DVD substrate produced a Raman signal 8.75-fold stronger than the silicon substrate. Furthermore, the SERS-DVD substrate yielded superior signal detection for commercial pesticide analytes (DDT and CaCO3) compared to the silicon substrate. These findings demonstrate the potential of SERS-DVD and ZnO thin film substrates for highly sensitive molecular detection, opening new avenues for research and development in detector technology operating at the molecular level.